Applying genetic epidemiology to explore sex-specific causes, correlations and consequences of obesity - Censin, JC (2021)
Obesity has considerable consequences on global health. Yet, it is relatively unexplored if the causes and consequences of obesity and obesity-related diseases differ between men and women. The increased scope of genetic studies provides an opportunity to leverage genetic data to characterise sex-specific epidemiological relationships using methods less prone to reverse causation and confounding, such as Mendelian randomisation. Thus, I aimed to investigate the sex-specific causes and consequences of obesity using genetic epidemiology, as well as to identify potential disease-mediating genes in two common obesity-related female reproductive diseases: polycystic ovary syndrome and miscarriage.